On the Abilities of Unconscious Freudian Motivational Drives to Evoke Conscious Emotions - Kirsch, Michael (Frontiers in Psychology, 2019)
Human beings use conscious emotions to direct their behaviours. There is some agreement in the scientific community that unconscious motivations are able to evoke conscious emotions. This manuscript focuses on Freudian motivational drives as inductors for unconscious motivation, and also on Panksepp’s framework of affective neuroscience for describing the generation of emotions. Recently, it has been suggested that imperative motor factors of Freudian drives (i.e. the hormones ghrelin, testosterone, angiotensin II and adenosine) have the ability to activate both a drive-specific brain area and brain areas of the SEEKING command system. In fact, this manuscript contends that all imperative motor factors have typical SEEKING targets (i.e. so-called receptors) in the brain areas of both nucleus accumbens and lateral hypothalamus. In addition, all imperative motor factors are able to target the central amygdala directly, a brain area classified by Panksepp as the instinctual part of the FEAR command system. Another point of interest may be the evaluation that imperative motor factors of the sexual drive, hunger and thirst can directly activate the RAGE command system by targeting the medial amygdala. Surprisingly, all imperative motor factors are able to modulate Panksepp’s granddaddy mechanism, i.e. to stimulate all seven command systems via the lateral hypothalamus. Orexinergic neurons exclusively located in the lateral hypothalamus have targets for imperative motor factors and project axons to characteristic brain areas of all seven command systems. From the fact that the imperative motor factors of the sexual drive and hunger act in an excitatory manner on orexinergic neurons whereas those of thirst and sleep inhibit such neurons, temporary termination of hunger by thirst may be understood as a very simple example of a co-regulation of Freudian drives. The author wishes to note that there are motivational drives other than the ones described by Freud. Bowlby was obviously the first in describing such drives, and Bowlbyian drive activities cannot be explained with the intermediacy of imperative motor factors. Nevertheless, the ignorance of the magnificent importance of imperative motor factors must be discarded.